Analysis of Deformation Characteristics of Surrounding Rock in Shallow Excavation Tunnel. Issue 6 (March 2019) - Yi, Qi; Ping, Wang
Abstract: This paper takes the section of the excavation section SK25+490 of Nanzhi Road Station of Harbin Metro Line 2 as the background. Through collecting field monitoring data, the diachronic variation curves of surface subsidence and vault subsidence are drawn. By using FLAC3D software, a 3d model is built based on the engineering profile of the tunnel. Through comprehensive comparison of numerical analysis results and field monitoring data, it is found that the deformation of tunnel surrounding rock can be divided into three stages: rapid deformation, slow growth and basic stability with the advance of palm face. The similarity between the field monitoring data and the numerical analysis of the surrounding rock deformation law is high, which is of guiding significance for the reasonable selection of construction methods and types of supporting lining.